(untitled) (Orfeu, 2025)
Could machines ever take our place in the creation of art, and particularly music? The outstanding results of some well-known AIs (e.g. EMI, Flow Machines) might make us believe that this is the case. However, despite this evidence it seems that machines present some intrinsic limits both in creative and non-creative contexts (already highlighted by John Searle and the debate around mechanism). The arguments of this paper are centered around this very belief: we are convinced that the utopian claims regarding all-round machine intelligence are not plausible and that our attention should be directed towards more relevant issues in the field of computational creativity. In particular, we focus our attention on what we call the “body issue”, i.e. the role of the body in the experience and creation of music, that we consider problematic for the idea of a truly creative machine (even if we take into consideration weaker renditions of artificial intelligence). Our argument is based on contemporary findings in neuroscience (especially on embodied cognition) and on the theories of Maurice Merleau-Ponty and Roland Barthes.